Green Marketing Strategy for Gaining Sustainable Competitive Advantage in Industry 4.0: Evidence from the Energy Sector - Ezrawati Nunut Nababan; Yodi Ibrahim; Judith Tagal Gallena Sinaga; Harman Malau (Journal of Educational Management Research, 2026)
This research is driven by global pressures on sustainability and the urgent need for clean energy transitions in the industrial sector, particularly in energy, during the Industry 4.0 era. Digital transformation and green marketing strategies are vital to improving operational efficiency, fostering environmentally friendly innovations, and building sustainable competitive advantage. This study aims to examine the influence of Green Marketing Orientation, Green Innovation, and Digital Marketing on Sustainable Competitive Advantage in energy sector companies in Indonesia within the decarbonization context. A quantitative approach was applied using a survey method and Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis on 50 managerial respondents from companies with environmental policies, decarbonization initiatives, and digital marketing platforms. Findings show that Green Marketing Orientation significantly and positively affects Green Innovation, Green Innovation significantly enhances Sustainable Competitive Advantage, and Digital Marketing has the strongest effect on competitive advantage, whereas the direct influence of Green Marketing on competitive advantage is not significant. The study concludes that integrating green strategy, innovation, and digital capabilities is essential to achieving sustainable competitive advantage, offering theoretical contributions to Resource-Based View and dynamic capabilities frameworks and practical implications for strategic corporate management in the decarbonization era.